As criptomoedas como expressões endêmicas do ciberespaço - Silva, André Torres da (2017)
The intention of this study was to investigate what are endemic expressions of cyberspace and what are their characteristics and impacts. We find in the current social experiences of the Internet that these are not only occurring between humans and their expressions - technologies and their effects - but there are also expressions that do not come from the physical world; Which arose and could only exist because of the very existence of cyberspace. However, even when exist cultural and communicational expressions that are endemic to cyberspace and cyberculture, in the readings on academic-scientific research dealing with the manifestations and interactions between the material and the digital world, what is commonly found are analyzes made about how material reality influences digital, that is, as cultural and communicational expressions that in the physical world form the outer layer of Cyberculture –the opposite of this study. In its, the research focused on the crypto-currencies, decentralized digital currencies, possessing a set of characteristics that demonstrate these cultural expressions native to cyberspace and cyberculture, where, perhaps the greatest exponent of this is the fact that besides cryptocurrency possesses other intrinsic characteristics, is both information itself and the medium in which it propagates. From this placement, a methodological design was proposed that began in a systematic review of the literature and developed with the hypothetical-deductive method, being also characterized by the exploratory bias, which revealed the impacts and effects that these technologies are producing in contemporary times. The theoretical basis used to base the study lead us to two directions, which were later found to be: communicational, with reference to the work of Marshall McLuhan, Robert K. Logan and Luiz Beltrão and, from a sociocultural perspective, those of Pierre Levy and Manuel Castells. From the economic point of view, the zero marginal cost perspective proposed by Jeremy Rifkin was used. In this way, it was presented how such manifestations overflow the cyberspace and directly affect the physical world in which we live, having real impacts that affect the economy, politics, culture and education in a global way, but also local - whose effects directly confront the status That the contemporary period is called by Jeremy Rifkin of the Third Industrial Revolution.